1996
DOI: 10.1002/(sici)1520-6769(199605)18:3<133::aid-nrc149>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Dopaminergic systems and parkinson's disease: Some latest developments in pathogenetic, diagnostic and pharmacotherapeutic investigations

Abstract: Patients suffering from Parkinson's disease (PD) display severe and progressive deficits in motor behavior, predominantly as a consequence of the degeneration of dopaminergic neurons, located in the mesencephalon and projecting to striatal regions. The cause of PD is still an enigma. In general, pharmacotherapy comprises symptomatic treatment with dopaminergic compounds, which induce a dramatic initial improvement, although serious problems gradually develop after longterm treatment. This paper describes some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Moreover in clinical trials, it has been seen that the vitamin E therapy has retarded the progression of degenerative process in PD patients [40, 41]. Vitamin E given with rotenone attenuated the rotenone-induced oxidative stress [42] and exhibits a dose dependent effect in PD patients [14]. Also, it has been reported that the levels of glutathione and vitamin E increased in the brain of patients with PD as a compensatory mechanism to deal with oxidative stress [41-43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover in clinical trials, it has been seen that the vitamin E therapy has retarded the progression of degenerative process in PD patients [40, 41]. Vitamin E given with rotenone attenuated the rotenone-induced oxidative stress [42] and exhibits a dose dependent effect in PD patients [14]. Also, it has been reported that the levels of glutathione and vitamin E increased in the brain of patients with PD as a compensatory mechanism to deal with oxidative stress [41-43].…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin E by virtue of its free radical scavenging ability efficiently reduced rotenone induced lipid peroxidation and ROS generated oxidative stress. Also, with vitmain E supplementation there is lesser utilisation of GSH and SOD or we can say that vitamin E replaced the protective enzymes and mechanisms that are deficient in nigral neurons thus sparing the scavenging systems i.e SOD and GSH from the injurious effects of neurotoxins like rotenone and 6-OHDA [40-42]. Thus, providing protection to the antioxidant defense system in dopaminergic neurons hence, lesser DA-nergic neurodegeneration [65].…”
Section: Discussionmentioning
confidence: 99%